Edible cookie cup: cuppa cookie / Raja Nur Hanisah Raja Zainal Alam Shah ... [et al.] - Raja Zainal Alam Shah, Raja Nur Hanisah; Ahmad Jamalulail, Nur Liyana A’tifah; Mohd Akram, Nur Farah Aqilah; Mohd Yusoff, Amera Nazirah; Omar, Noorshaadah (2021)
Based on the research that we have conducted, the article concludes that plastic cup consumption is increasing in our daily lives. Many Malaysians enjoy drinking Starbucks coffee or any other sort of coffee brand on a daily basis. This will result in an increase in plastic waste generated by Malaysian consumers. As a result of this problem, we decided to create Cuppa Cookies, often known as edible cookie cups. Following that, Cuppa Cookies is an alternative effort to reduce disposable cup usage in Malaysia. This edible cookie cup is a one-of-a-kind way to present beverages and sweet treats together. We noticed that our product can provide benefits to the consumer and also can give a positive impact on the environment. Additionally, our product, which is Cuppa Cookies, is made with premium quality cookie dough and comes in two flavors: premium classic cookie and premium dark chocolate cookie. Next, our product is safe for people of all ages to consume because we do not use any harmful ingredients. Besides, Cuppa Cookies are excellent for people who wish to maintain a healthy lifestyle because they offer dark chocolate flavors. Furthermore, the consumer could enjoy any beverage in Cuppa Cookies, then they could eat the cup once they finished their drinks. Next, we also create a cup lid out of cookies to prevent water spillage and we also provide a biodegradable cup sleeve at the bottom of the Cuppa Cookies to maintain the hygiene of our product. Lastly, the most important part is Cuppa Cookies does not alter the flavor of beverages due to the fact that we use premium quality cookie dough.